Atrophy of specific amygdala subfields in subjects converting to mild cognitive impairment - Caterina Padulo; Carlo Sestieri; Miriam Punzi; Eleonora Picerni; Piero Chiacchiaretta; Maria Giulia Tullo; Alberto Granzotto; Antonello Baldassarre; Marco Onofrj; Antonio Ferretti; Stefano Delli Pizzi; Stefano L. Sensi; et al. (Alzheimer’s & Dementia: Translational Research & Clinical Interventions, 2023)
Abstract Introduction Accumulating evidence indicates that the amygdala exhibits early signs of Alzheimer's disease (AD) pathology. However, it is still unknown whether the atrophy of distinct subfields of the amygdala also participates in the transition from healthy cognition to mild cognitive impairment (MCI). Methods Our sample was derived from the AD Neuroimaging Initiative 3 and consisted of 97 cognitively healthy (HC) individuals, sorted into two groups based on their clinical follow‐up: 75 who remained stable (s‐HC) and 22 who converted to MCI within 48 months (c‐HC). Anatomical magnetic resonance (MR) images were analyzed using a semi‐automatic approach that combines probabilistic methods and a priori information from ex vivo MR images and histology to segment and obtain quantitative structural metrics for different amygdala subfields in each participant. Spearman's correlations were performed between MR measures and baseline and longitudinal neuropsychological measures. We also included anatomical measurements of the whole amygdala, the hippocampus, a key target of AD‐related pathology, and the whole cortical thickness as a test of spatial specificity. Results Compared with s‐HC individuals, c‐HC subjects showed a reduced right amygdala volume, whereas no significant difference was observed for hippocampal volumes or changes in cortical thickness. In the amygdala subfields, we observed selected atrophy patterns in the basolateral nuclear complex, anterior amygdala area, and transitional area. Macro‐structural alterations in these subfields correlated with variations of global indices of cognitive performance (measured at baseline and the 48‐month follow‐up), suggesting that amygdala changes shape the cognitive progression to MCI. Discussion Our results provide anatomical evidence for the early involvement of the amygdala in the preclinical stages of AD. Highlights Amygdala's atrophy marks elderly progression to mild cognitive impairment (MCI). Amygdala's was observed within the basolateral and amygdaloid complexes. Macro‐structural alterations were associated with cognitive decline. No atrophy was found in the hippocampus and cortex.